Effects of Ramadan fasting on training induced adaptations to a seven-week high-intensity interval exercise programme - Aziz, A. R.; Slater, G. J.; Chia, M.Y.H.; Teh, K.C. (Science & Sports, 2012)
Objectives: The purpose of this study was to determine if aerobic and anaerobic training-induced adaptations were compromised as a result of Ramadan fasting. Methods: Twenty adolescent males of the Muslim and non-Muslim faith were divided into fasting (FAS, n = 10) and non-fasting or control (CON, n = 10) groups, respectively. High-intensity interval cycle exercise training was conducted three times per week for seven weeks, with Ramadan fasting falling during training weeks 3 to 6 for the FAS group. Results: Both groups significantly improved their peak oxygen uptake (VO2peak; FAS 2.77 ± 0.33 to 3.08 ± 0.22 and CON 2.61 ± 0.22 to 2.89 ± 0.21 L/min) and maximal anaerobic performance (total work during four Wingate bouts; FAS 53.4 ± 5.2 to 57.7 ± 4.8 and CON 47.4 ± 4.5 to 52.0 ± 4.5 kJ) (all p < 0.05). There were no significant differences in the magnitude of improvements made between groups, either for aerobic (FAS 0.31 ± 0.28 vs. CON 0.28 ± 0.12 L/min) or anaerobic (FAS 4.3 ± 3.3 vs. CON 4.6 ± 3.4 kJ) performance (all p > 0.05). Indices of training intensity (mean heart rate and mean blood lactate) and mean daily energy and fluid intake were not significantly different between groups throughout the study period. Conclusions: Aerobic and anaerobic adaptations to seven weeks of training were not compromised by four weeks of intermittent Ramadan fasting, possibly because the overall training intensity and nutrient intake were maintained throughout the Ramadan period.